A bibliometric analysis of COVID-19's impact on the sharing economy. (14th September 2022) - Feng, Jian; Liu, Zhenfeng
A rapidly growing body of scholarly research discusses the impact of the COVID-19 pandemic on the sharing economy (SE). This study aims to employ bibliometric analysis to examine the research themes, scholarly communities, evolution paths and research hotspots of the developing domain of COVID-19's SE research. Adopting an integrated bibliometric approach, this study analyses articles published on Web of Science from 2008 to 2019 and from 2020 to 2021. The outcomes of this study reveal that four new research themes including the COVID-19's impact were updated for the post-pandemic SE research. The scholarly communities' analysis identifies research changes of documents and published journals communities of COVID-19. The results also dig into the evolution path of the topic and instigate further research hotspots toward SE activities. Thus, we contribute to point out the research directions for the opportunities and challenges of SE after the COVID-19 pandemic.